Application of multiple machine learning approaches to determine key pyroptosis molecules in type 2 diabetes mellitus - Wang, Min; Wu, He; Wu, Ronghua; Tan, Yongshun; Chang, Qingqing (Frontiers in Endocrinology, 2023)
Objective: Pyroptosis, a lytic and inflammatory programmed cell death, which has been implicated in type 2 diabetes mellitus (T2DM) and its complications. Nonetheless, it remains elusive exactly which pyroptosis molecule exerts an essential role in T2DM, and this study aims to solve such issue. Methods: Transcriptional profiling datasets of T2DM: GSE20966, GSE95849, and GSE26168 were acquired. Four machine learning models: random forest, support vector machine, extreme gradient boosting, and generalized linear modeling were built based upon pyroptosis genes. A nomogram of key pyroptosis genes was also generated, and the clinical value was appraised via calibration curves and decision curve analysis. Immune infiltration was inferred utilizing CIBERSORT. Drug-druggable target relationships were acquired from the Drug Gene Interaction Database. Through WGCNA, key pyroptosis genes-relevant genes were selected. Results: Most pyroptosis genes exhibited the up-regulation in T2DM relative to controls, indicating the activity of pyroptosis in T2DM. The SVM model composed of BAK1, CHMP2B, NLRP6, PLCG1, and TIRAP exhibited the best performance in T2DM diagnosis, with AUC = 1. The nomogram can predict the risk of T2DM for clinical practice. NK cells resting exhibited the lower abundance in T2DM versus normal specimens, with the higher abundance of neutrophils. NLRP6 was positively linked with neutrophils. Drugs (keracyanin, 9,10-phenanthrenequinone, diclofenac, phosphomethylphosphonic acid adenosyl ester, acetaminophen, cefixime, aspirin, ustekinumab) potentially targeted the key pyroptosis genes. Additionally, CHMP2B-relevant genes were determined. Conclusion: Altogether, this work proposes the key pyroptosis genes in T2DM, which might become possible molecules for the management and treatment of T2DM and its complications.